UiTM News Hub: The Global Insights Essay Contest 2023 / Fazmawati Zakaria - Zakaria, Fazmawati (2023)
Arau, 26 May 2023 - The Academy of Language Studies and Student Affairs Division, UiTM Perlis Branch together with University of Finance and Economics (UFE), Mongolia held their annual essay competition last month. The purposes of this program are to strengthen collaboration and cooperation between UiTM and UFE, to enhance students' academic performance through international competition and to showcase students' academic skills and knowledge.